FAKTOR-FAKTOR YANG MEMENGARUHI PERGANTIAN AUDITOR PADA PERUSAHAAN NON KEUANGAN - MAHARANI BINTANG DWI MILLENNIUM; Dewi Kurnia Indrastuti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This research paper’s purpose is to empirically examine the influence of the independent variables financial distress, client size, audit firm size, ownership concentration, management change, audit opinion, and profitability on auditor switching. The non-financial public listed companies that are consistently listed in The Indonesian Stock Exchange (IDX) from the year 2015 to 2019 are the population of this research. The number of samples used in this research is 125 samples based on the purposive sampling method. The hypothesis was tested using logistic regression. The result shows that audit firm size has an influence on auditor switching. Companies that use the big four Public Accountant Firm audit services will retain their auditors caused of the credibility and good reputation of the big four Public Accountant Firm. While financial distress, client size, ownership concentration, management change, audit opinion, and profitability have no influence on auditor switching.